Global Perspectives on Addressing Systemic Issues in Music Therapy Curricula and Healthcare - Amy Clements-Cortés; Melissa Mercadal-Brotons; Hakeem Leonard; Vivian Chan; Gro Trondalen; Tao-Deva Stingl; Thomas Stegemann; Claudia Zanini (Voices)
The discipline of music therapy is practiced differently across the globe and over the years, in all regions of the world, the number of music therapy training programs has expanded. As such, there is a need to reflect on the differences between education and training programs, which vary according to the local culture, educational needs, theoretical background, and scope, among others. Music  therapists work in a variety of environments including hospitals, community centres, regular or special education schools, speciality clinics, private practice, and long-term care homes, etc. Music therapists are tasked with navigating policies in their workplaces and balancing the needs of their clients/consumers/service users. This article written together by educators and a student aims to present brief highlights of the work of the authors whose collaboration resulted in a presentation at the European Congress of Music Therapy in June 2022. This presentation focused on the challenges and issues faced by the discipline of music therapy and health in general, based on the analysis of systemic issues in education and training, social issues, and significant issues such as multiculturalism, equity, and race around the world. These were identified as important issues for the authors who desired to raise awareness on these topics to further open ongoing dialogue. Our aim is to contribute to the establishment of dialogues between music therapy educators, allied health professionals, researchers, and students for the implementation of new courses and the updating of existing programs, expanding views on possible music therapy interventions in contemporary times.